KAYU KELAPA SEBAGAI BAHAN INTI PAPAN BLOK - Suwandi Kliwon; Paribotro Sutigno; M I lskandar (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
This report deals with the making of blackboard with coconut wood core and testing the physical and mechanical properties of the blackboard. The coconut wood (Cocos nucifera) was collected from Banten, (West Java).The results, indicate that the physical properties of blockboard with coconut wood core are worse than that with a mixture of red meranti and coconut wood core. The bending strength paralel to the grain of blockboard with coconut wood core is better than that with a mixture of coconut wood and meranti wood, while the properties perpendicular to the grain do not show significant difference.Only the glue shear strength of blockboard type II with a mixture of coconut wood and red meranti wood core is in compliance with Indonesian and Japanesse (JAS) standars.